Genetic polymorphisms in TLR1, TLR2, TLR4, and TLR10 of Helicobacter pylori-associated gastritis: a prospective cross-sectional study in Thailand. Issue 2 (March 2018) - Tongtawee, Taweesak; Bartpho, Theeraya; Kaewpitoon, Soraya; Kaewpitoon, Natthawut; Dechsukhum, Chavaboon; Leeanansaksiri, Wilairat; Loyd, Ryan A.; Talabnin, Krajang; Matrakool, Likit; Panpimanmas, Sukij
Abstract : The toll-like receptors (TLRs) mediate the recognition of Helicobacter pylori and initiate the innate immune response to infection. We hypothesized those genetic polymorphisms in the TLR1, TLR2, TLR4, and TLR10 influence bacterial infection, affecting susceptibility H. pylori to disease outcomes. Genomic DNA was extracted and genotypes of TLR1 ( rs4833095 ), TLR2 ( rs3804099 and rs3804100 ), TLR4 (rs10759932), and TLR10 ( rs10004195 ) polymorphism were detected by the TagMan single-nucleotide epolymorphisms genotyping assay using the real-time PCR hybridization probe method. The TLR1 ( rs4833095 ), C allele and the TLR10 ( rs10004195 ), A allele frequency was significantly increased risk in the H. pylori infection group (odds ratio=1.76, 95% confidence interval=1.84–2.15, P =0.01 and odds ratio=1.81, 95% confidence interval=1.18–3.26, P =0.04, respectively). The TLR1 ( rs4833095 ), C allele and TLR10 ( rs10004195 ), A allele are susceptible TLRs polymorphisms in the Thai population. These findings suggest that TLR1 rs4833095 and TLR10 rs10004195 may play crucial roles in H. pylori susceptibility and gastric pathogenesis.